A kinder, gentler democracy? - Needs and ambitions - Lewin, Leif (Uppsala University, 2015)
The project is a joint venture between the Faculties of Social sciences and Medicine at Uppsala University. We try to explain the variation between Swedish municipalities regarding their care for persons with disabilities and we search for the explanation in a much esteemed political science theory on so called consensus democracy. The theory states that if the relation between political parties is characterized by cooperation instead of conflict, it leads to a ”kinder, gentler form of democracy” for vulnerable groups, for instance persons with disabilities (Lijphart). The Political science department is the main seat of the project. It has long experience of the theory and also a large data base on consensus democracy at the municipal level. A great part of the research will be conducted at the Centre for disability research where there is intimate knowledge of such material that will constitute the dependent variable. The study is a total investigation, supplemented with qualitative case studies. The study involves testing of hypotheses. It also allows testing of counter hypotheses such as the importance of ideology or political party.

Purpose:

The aim of this research project is to find the causes of regional variation in disability policies.

Contains variables used for the article:
Lewin, B. Westion, L. and Lewin, L. (2008) "Needs and Ambitions in Swedish Disability Care", Scandinavian Journal of Disability Research, 10:4, 237-58. DOI:10.1080/15017410802410068

Projektet är ett samarbete mellan de Samhällsvetenskapliga och Medicinska fakulteterna vid Uppsala universitet, och syftar till att förklara variationen mellan de svenska kommunerna i omsorgen om de funktionshindrade. Förklaringen söks i den uppburna statsvetenskapliga teorin om s.k. samarbetsdemokrati, vilken sägs leda till en "mänskligare, mera omtänksam demokrati" för utsatta grupper, bl.a. funktionshindrade (Lijphart). Huvudhemvist är Statsvetenskapliga institutionen med lång erfarenhet av och databas om samarbetsdemokrai på kommunal nivå men en stor del av forskningen utförs vid Centrum för handikappforskning med dess förtrogenhet med sådant material, som läggs till grund för den beroende variabeln. Undersökningen är en totalundersökning av svenska kommuner, kompletterad med kvalitativa fallstudier. Studien är hypotesprövande; den är så upplagd att även mothypoteser såsom betydelsen av ideologi och parti kan testas.

Syfte:

Syftet med forskningsprojektet är att finna orsakerna till den regionala variationen i handikappolitiken.

Innehåller de variabler som används för artikeln:
Lewin, B. Westion, L. and Lewin, L. (2008) "Needs and Ambitions in Swedish Disability Care", Scandinavian Journal of Disability Research, 10:4, 237-58. DOI:10.1080/15017410802410068
En mänskligare demokrati? Handikappolitiken i svenska kommuner. - Needs and ambitions i projektet En mänskligare demokrati?
Keywords: local government policy; kommunalpolitik; care of the disabled; handikappomsorg; democracy; demokrati; local government organizations; kommunala organisationer; social support; socialt stöd; political systems; politiska system; right to non-discrimination; rätten till likabehandling; social welfare philosophy; social välfärdsfilosofi; cooperation; samarbete; welfare policy; social- och välfärdspolitik; Government, political systems and organisations; Regering, politiska system och organisationer; Social welfare policy; Välfärdspolitik; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap